The Singapore biotechnology industry - Wang, Jie (2008)
This research sets to examine the industrial success factors and identify the constraints on Singapore’s biotechnology industry by asking biotechnology companies (both the local and foreign companies) to identify the importance level and current status of each factor. The case studies were conducted with managers of the biotech companies in Singapore.